2018
DOI: 10.1002/bse.2231
|View full text |Cite
|
Sign up to set email alerts
|

Buyer–supplier collaboration in green practices: The driving effects from stakeholders

Abstract: Green and environmental practices are considered critical to enhancing firm innovation and performance. Previous research has not fully explained how and why buyers collaborate with suppliers in green practices. This study aimed to verify the driving effects of stakeholders and the underlying mechanism in buyer–supplier collaboration. Questionnaires were used to collect empirical data from selected purchasing managers in listed Taiwanese electronics firms. Structural equation modeling was used to analyze the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 143 publications
(206 reference statements)
4
55
0
1
Order By: Relevance
“…Consistent with these arguments, Yen (2018) and others (e.g., Lee, 2008; Liu, Yang, Qu, Wang, Shishime, & Bao, 2012) find a significant impact of customer demands on buyer–supplier collaboration in the green practices of Chinese firms. Furthermore, the study shows an indirect effect of competitor pressure (through customer pressure) on environmental buyer–supplier collaboration, which means that “once customers have detected competing suppliers with superior green practices, they force their current suppliers to keep pace with or even outperform the competitive suppliers” (Yen, 2018, p. 8).…”
Section: Literature Reviewmentioning
confidence: 74%
“…Consistent with these arguments, Yen (2018) and others (e.g., Lee, 2008; Liu, Yang, Qu, Wang, Shishime, & Bao, 2012) find a significant impact of customer demands on buyer–supplier collaboration in the green practices of Chinese firms. Furthermore, the study shows an indirect effect of competitor pressure (through customer pressure) on environmental buyer–supplier collaboration, which means that “once customers have detected competing suppliers with superior green practices, they force their current suppliers to keep pace with or even outperform the competitive suppliers” (Yen, 2018, p. 8).…”
Section: Literature Reviewmentioning
confidence: 74%
“…The concern about an economic crisis, associated with positive feelings aroused by the admiration of those working during the pandemic, may explain this solidarity. Some studies state and discuss consumers’ appreciation of charitable and sustainable companies (e.g., through green buying) ( Yen, 2018 ). As expected, unemployed consumers do not show the inclination to solidarity since they are in an unfavorable situation, and social inequality undermines solidarity ( Mishra & Rath, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to ensure the greenness of the supply chain, multinational enterprises cannot only concentrate on their suppliers, they also need to ensure that their second‐tier suppliers and their suppliers are environmentally responsible. This notion has empirical support (Caniëls, Gehrsitz, & Semeijn, ) and, for example, Yen (, p. 1669) found that customer pressure “positively influences buyer‐supplier collaboration in green practices.” Thus, small manufacturing firms with well‐developed GPC will be attractive to multinational enterprises trying to minimize their environmental footprint. Being attractive is the first step; the customers must also be aware of the firm's attractiveness for this to result in economic growth.…”
Section: Theory and Hypothesesmentioning
confidence: 95%